An additional species of the genus Nemaspela Šilhavý, 1966 from a cave in Georgia, with a note on Nemaspela melouri (Opiliones: Nemastomatidae) - Martens, Jochen; Maghradze, Eter; Barjadze, Shalva (Zootaxa, 2023)
A cavernicolous harvestman species, Nemaspela kotia sp. nov., is described from the Kotia Cave (=Kotiasklde Cave) in Zemo Imereti plateau, Imereti Region, West Georgia. Its males lack a cheliceral apophysis, a feature shared with the Georgian cave-dwelling Nemaspela femorecurvata Martens, 2006 and N. prometheus Martens, Maghradze & Barjadze, 2021. Besides, Nemaspela melouri Martens, Maghradze & Barjadze, 2021, known only from its type locality, is found in Solkota Cave (Tskaltubo Municipality, Sataplia-Tskaltubo karst massif, Imereti region, West Georgia). A key for the identification of the known species of Nemaspela is provided.